Health-Care Workers' Perception of Patients' Suicide Intention and Factors Leading to It: A Qualitative Study. (December 2020) - Wee, Lei-Hum; Ibrahim, Norhayati; Wahab, Suzaily; Visvalingam, Uma; Yeoh, Seen Heng; Siau, Ching Sin
This study explored health-care workers' perception of patients' suicide intention and their understanding of factors leading to particular interpretations. Semistructured face-to-face in-depth interviews were conducted with 32 health-care workers from a general hospital in Klang Valley, Malaysia. Interview data were transcribed verbatim and analyzed using the interpretative phenomenological analysis. The health-care workers were found to have four types of perceptions: to end life, not to end life, ambivalence about intention, and an evolving understanding of intention. Factors leading to their perceptions of patients' suicide intention were patient demographics, health status, severity of ideation/attempt, suicide method, history of treatment, moral character, communication of suicide intention, affective/cognitive status, availability of social support, and health-care workers' limited knowledge of patients' condition/situation. Insufficient knowledge and negative attitudes toward suicidal patients led to risk minimization and empathic failure, although most health-care workers used the correct parameters in determining suicide intention.